Long read transcriptome sequencing of a sugarcane hybrid and its progenitors, Saccharum officinarum and S. spontaneum - Thirugnanasambandam, Prathima Perumal; Singode, Avinash; Thalambedu, Lakshmi Pathy; Athiappan, Selvi; Krishnasamy, Mohanraj; Purakkal, Sobhakumari Valiya; Govind, Hemaprabha; Furtado, Agnelo; Henry, Robert (Frontiers in Plant Science, 2023)
Commercial sugarcane hybrids are derivatives from Saccharum officinarum and Saccharum spontaneum hybrids containing the full complement of S. officinarum and a few S. spontaneum chromosomes and recombinants with favourable agronomic characters from both the species. The combination of the two sub-genomes in varying proportions in addition to the recombinants presents a challenge in the study of gene expression and regulation in the hybrid. We now report the transcriptome analysis of the two progenitor species and a modern commercial sugarcane hybrid through long read sequencing technology. Transcripts were profiled in the two progenitor species S. officinarum (Black Cheribon), and S. spontaneum (Coimbatore accession) and a recent high yielding, high sugar variety Co 11015. The composition and contribution of the progenitors to a hybrid with respect to sugar, biomass and disease resistance were established. Sugar related transcripts originated from S. officinarum while several stress and senescence related transcripts were from S. spontaneum in the hybrid. The hybrid had a higher number of transcripts related to sugar transporters, invertases, transcription factors, trehalose, UDP sugars and cellulose than the two progenitor species. Both S. officinarum and the hybrid had an abundance of novel genes like sugar phosphate translocator, while S. spontaneum had just one. In general, the hybrid shared a larger number of transcripts with S. officinarum than with S. spontaneum reflecting the genomic contribution, while the progenitors shared very few transcripts between them. The common isoforms among the three genotypes and unique isoforms specific to each genotype indicate that there is a high scope for improvement of the modern hybrids by utilizing novel gene isoforms from the progenitor species.